Photobleaching of ultrashort pulses with different repetition rates in two-photon excitation microscopy. (12th March 2019) - Niu, Fuzeng; Wu, Runlong; Wu, Danlei; Gou, Dongzhou; Feng, Lishuang; Chen, Liangyi; Zhang, Zhigang; Wang, Aimin
Abstract: Photobleaching of fluorescent specimens with the excitation of different repetition rate ultrafast fiber lasers was studied and demonstrated in two-photon excitation microscopy. A higher repetition rate is proved to induce a lower grade photobleaching for the same imaging contrast. In detail, 750 MHz can reduce the photobleaching rate by ~3 fold compared to 22 MHz, and by ~2 fold compared to 94 MHz. This was underpinned by the testing of fixed zebrafish heart tissue slices. Furthermore, we highlight the advantages of a high repetition rate fiber laser in two-photon, long-time biological in vivo imaging, with a lower photobleaching rate and suitable fluorescence signal intensity.